Impact of Soil Compaction on Bulk Density and Root Biomass of Quercus petraea L. at Reclaimed Post-Lignite Mining Site in Lusatia, Germany - Eric K. A. Twum; Seth Nii-Annang (Applied and Environmental Soil Science)
The impact of soil compaction on bulk density and root biomass of Quercus petraea L. was assessed after 85 years of reclamation of post-lignite mining soil at Welzow-South, in Lusatia, Germany. Bulk density of core soils sampled from 20 to 25 cm, 100 to 105 cm, and 200 to 205 cm depths and oven-dried biomass of Q. petraea roots sampled from 0 to 30 cm and at successive depths of 20 cm, up to 210 cm depth at compacted and uncompacted sites were determined. Bulk density was significantly higher at 20 to 25 cm (1.74±0.09 g cm−3) and 100 to 105 cm (1.65±0.06 g cm−3) depths of the compacted site. Likewise, compaction induced significant greater root biomass within the 0 to 70 cm depth with higher bulk density; root biomass at this depth was 2-fold greater compared to the uncompacted site. Root biomass decreased with soil depth and showed significant relationship with depth at both sites. The result indicates that, after 85 years of reclamation, the impact of soil compaction persisted as evident in higher bulk density and greater root biomass.